Training on the Use of Report Application Based on Ms. Excel with Curriculum 2013 for Teachers of SDN 105 Kendari - Sari, Jayanti Yusmah; Pasrun, Yuwanda Purnamasari; Muchtar, Mutmainnah (MEKONGGA: Jurnal Pengabdian Masyarakat, 2024)
The implementation of the 2013 Curriculum (K-13) in elementary schools (SD) has brought significant changes to teachers' administrative activities, especially in filling out student report cards, which are now more complex compared to the previous curriculum. To facilitate the process of entering report card grades, teachers were provided with a report card application based on Microsoft Excel. However, at SDN 105 Kendari, most teachers encountered difficulties using the application due to limited technological knowledge, resulting in the report card process often being assisted by the school operator. To address this issue, the Faculty of Information Technology at Universitas Sembilanbelas November Kolaka organized training on the use of the K-13 report card application based on Microsoft Excel for the teachers at SDN 105 Kendari. The training was conducted in person, actively involving participants in each stage. The training covered an introduction to basic Microsoft Excel formulas and detailed use of the K-13 report card application. The results showed that the program ran smoothly and received positive feedback from the participants. It is hoped that the teachers will become more independent and efficient in filling out student report cards.